Aspirin suppresses NFκB1 expression and inactivates cAMP signaling pathway to treat atherosclerosis. (11th January 2019) - Zhang, Liping; Li, Te; Miao, Xiao; Ding, Lijuan; Wang, Shudong; Wang, Yonggang
Abstract: Aspirin showed both favorable efficacy and safety in the treatment of atherosclerosis (AS). This study aimed to explore the effects of Aspirin on AS treatment. Differentially expressed mRNAs in AS were screened out and visualized by R project. The mRNA expression levels of NFκB1 and its targets were detected by qRT‐PCR. The protein expression levels of NFκB1, intercellular cell adhesion molecule‐1 ( ICAM1 ) and vascular cell adhesion molecule‐1 ( VCAM1 ) were detected by western blot analysis. Besides, CCK‐8 and flow cytometry assay were employed to evaluate the effects of Aspirin on cell proliferation rate and cell apoptotic rate respectively. Mouse model of AS was established for the verification of Aspirin‐mediated suppression of AS progression in vivo. NFκB1 and Anti‐Mullerian Hormone ( AMH ) were both over‐expressed in atherosclerotic femoral artery tissues compared with healthy femoral artery tissues. cAMP signaling pathway was activated in AS. Overexpression of NFκB1 largely increased cell proliferation rate of VSMCs, which was instead down‐regulated with suppression of NFκB1 in AS. By contrast, down‐regulation of NFκB1 greatly increased cell apoptotic rate of VSMCs, which was otherwise reversed with up‐regulation of NFκB1 in AS. It was proved that Aspirin increased cell apoptotic rate yet decreased cell proliferation rate of VSMCs to suppress AS progression by down‐regulating the expression of NFκB1 and its targets, which might well provide us with more therapeutic strategies for treatment of AS. © 2019 BioFactors, 45(3):343–354, 2019